2017
DOI: 10.1002/hep.29337
|View full text |Cite
|
Sign up to set email alerts
|

Prospero‐related homeobox 1 drives angiogenesis of hepatocellular carcinoma through selectively activating interleukin‐8 expression

Abstract: We have identified PROX1 as a crucial promoter of HCC angiogenesis; our study provides an insight into PROX1's function in HCC progression and the potential therapeutic application of anti-IL-8 antibody in high PROX1 expression HCC patients. (Hepatology 2017;66:1894-1909).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
1
25
0
1
Order By: Relevance
“…In HCC, USP7 was highly expressed in cancer tissues [15]. USP7 could inhibit the ubiquitination of P65 and stabilize the expression of P65, thereby promoting the progress of hepatoma cancer [16]. In addition, reported data supports that USP7 can be used as a new independent prognostic factor for liver cancer [17].…”
Section: Introductionmentioning
confidence: 67%
“…In HCC, USP7 was highly expressed in cancer tissues [15]. USP7 could inhibit the ubiquitination of P65 and stabilize the expression of P65, thereby promoting the progress of hepatoma cancer [16]. In addition, reported data supports that USP7 can be used as a new independent prognostic factor for liver cancer [17].…”
Section: Introductionmentioning
confidence: 67%
“…WWOX, a gene bearing the WW domain, straddles a very common chromosomal fragile site (FRA16D) which is known to be altered in various types of cancers . Addressing the vital role of angiogenesis is important in the process of tumorigenesis and the metastasis or recurrence in HCC . Previous studies showed that low WWOX expression may aid in the promotion of angiogenesis in various cancers, and also showed that the methylation of WWOX gene promoter CpG island was associated with suppression of WWOX expression .…”
Section: Discussionmentioning
confidence: 99%
“…PROX1 is a nuclear transcription factor associated with the embryonic development of multiple organs, including the central nervous system, heart, lymphatic system, skeletal muscles, lens, retina, and so on [102]. Reportedly, PROX1 plays various tumor-dependent functional roles, which reflect both the oncogenic potential and a tumor-suppressive role [90].…”
Section: Novel Prognosticators Of Osccmentioning
confidence: 99%
“…Reportedly, PROX1 plays various tumor-dependent functional roles, which reflect both the oncogenic potential and a tumor-suppressive role [90]. In addition, PROX1 promoted cell growth, angiogenesis, and sorafenib resistance in patients with HCC [102,91] and is associated with the lymphangiogenesis, metastasis, and poor prognosis in various malignancies [92,103,104]. However, high PROX1 expression is related to better prognosis for pancreatic and gastric cancer patients [105,106].…”
Section: Novel Prognosticators Of Osccmentioning
confidence: 99%